Study on Sitting Postures Recognition in Pressure Cushion - Bao, Jun Rong; Bao, Chong Zhi; Li, Jian (Applied Mechanics and Materials, 2013)
Sitting postures affect their safety in wheelchair for persons with the disability or the ender people. In this paper, it is explored the relationship between the pressure distributions and sitting posture; using density-based clustering methods establish the evaluation model. Real instance verify that the model can accurately predict the relations between pressure distribution and sitting postures.